(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Crystal engineering is a field focused on designing and developing molecular solid particles with desired properties and functionalities. The crystal habit and polymorphic form of a substance play a crucial role in determining its physicochemical, mechanical, and biological behavior. Modifying the crystal habit alone can lead to the formation of distinct morphological forms, which directly influence particle orientation. Such alterations significantly affect critical parameters including flowability, packing density, compressibility, syringebility, and dissolution behavior of pharmaceutical powders. Particle size enlargement is typically accomplished through established conventional techniques, which are widely adopted in pharmaceutical manufacturing. The main objective of this study was to formulate sphere shaped crystal agglomerates of Darunavir Ethanolate (DRVE) having enhanced flowability, compression ability, solublisation property and dissolution. DVRE spherical crystals were developed by using 22 full factorial design approach. Plasdone 630 as polymer and methylene dichloride (MDC) as bridging solvent were considered as independent variables and their effect was studied on drug content and solubility considering as a dependent variable. The optimised spherical crystals were used in tablet formulations. The drug content of the spherical agglomerates ranged between 89.80 (SAD6) to 95% (SAD2). The solubility of the spherical agglomerates was ranged between 0.20 (SA6) to 1.80 mg/ml (SAD2) with 11.25-fold enhancement in solubility. FTIR study indicated the excellent compatibility of the drug with polymer used in formulation. XRD study suggested the amorphization of pure DVRE during the agglomeration process. The optimised SA2 spherical agglomerates were used to manufacture immediate release tablets by DC method (F1). Presence of spherical agglomerates has significantly improved the flow properties as well as compressibility of the blend in comparison pure DVRE. The drug release of F1 batch was found to be faster in comparison to F2 and F3 formulations. Nearly 100% release was observed within 15 minutes from F1. The study concludes that the use of spherical agglomerates leads to enhanced flow properties, compressibility, solubility, and dissolution behavior.